Chia and quinoa byproducts as potential antioxidants for the meat industry - Strashynskyi, Igor; Fursik, Oksana; Shevchenko, Tatiana (My University, 2021)
In the diet of the population, products such as chia seeds and quinoa began to appear more and more often. In addition to the use of chia seeds, processed products such as oil and fiber are becoming popular, which can also be used in technologies for making daily products.
Keywords: кафедра технології м’яса і м’ясних продуктів; chia seeds; quinoa; cellulose; meat industry